Pembinaan dan Pengawasan Pencetakan Al-Qur'an di Indonesia - Dwi Martiningsih (SUHUF, 2020)
This article explains the problems of guidance and supervision to the publication of the Indonesian mushaf which is conducted by the Board of Correction of the Mushaf (Lajnah Pentashihan Mushaf Al-Qur'an - LPMQ) as the technical implementing unit in the Ministry of Religious Affairs of the Republic of Indonesia. The LPMQis responsive to the development of technology. One of the proofs is to conduct the system of mushaf correction (tashih) via online. The publishers, printers, distributors and users of the Qur’an become the partners of the LPMQ in performing its various duties and functions. The mushaf is the sacred thing which in its production needs high accuracy. However, the fact is that the mistakes in the process of printings often occurred for many reasons. On the other hand, the government policy concerning the action to such mistakes is considered to be lack of firm, so that it does not have a deterrent effect. Thus, the policy makers need to implement a more intensive system to monitor the publishers and the printers of the mushaf in Indonesia. The guidance andsupervision is supposed not only focusing on the product of the mushaf but also on the process of management of the publishers wholly